2021
DOI: 10.3389/fmicb.2021.723187
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis DSM29784 Alleviates Negative Effects on Growth Performance in Broilers by Improving the Intestinal Health Under Necrotic Enteritis Challenge

Abstract: Along with banning antibiotics, necrotic enteritis (NE), especially subclinical enteritis (SNE), poses a significant threat to the chicken industry; however, probiotics are a potentially promising intervention. We aimed to investigate the beneficial effects of Bacillus subtilis DSM29784 (BS) on the treatment of Clostridium perfringens (CP)-induced SNE in broilers. A total of 360 1-day-old broiler chicks were divided into three treatment groups, namely control (Ctr), SNE, and BS treatment (BST) groups, all of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 89 publications
(87 reference statements)
0
32
0
Order By: Relevance
“…Research indicated that the antibacterial substances produced by Bacillus have broad-spectrum bactericidal activity and have strong bactericidal effects on many food-related bacteria ( Jones and Knight, 2012 ). Moreover, Bacillus could produce beneficial metabolites such as vitamins, showing great potential in alleviating the gut microbial dysbiosis and treating bacterial infections ( Li Y. T. et al, 2019 ; Wang et al, 2021 ). In this study, we also found that LPS exposure resulted in a significant increase in some pathogenic bacteria such as Klebsiella , Helicobacter and Enterococcus .…”
Section: Discussionmentioning
confidence: 99%
“…Research indicated that the antibacterial substances produced by Bacillus have broad-spectrum bactericidal activity and have strong bactericidal effects on many food-related bacteria ( Jones and Knight, 2012 ). Moreover, Bacillus could produce beneficial metabolites such as vitamins, showing great potential in alleviating the gut microbial dysbiosis and treating bacterial infections ( Li Y. T. et al, 2019 ; Wang et al, 2021 ). In this study, we also found that LPS exposure resulted in a significant increase in some pathogenic bacteria such as Klebsiella , Helicobacter and Enterococcus .…”
Section: Discussionmentioning
confidence: 99%
“…An increased abundance in bacteria of the genus Eisenbergiella has been associated with reduced incidence of gastrointestinal disorders linked to metabolic and microbiota changes (functional dyspepsia), resulting in improved nutrient metabolism in broiler chickens [ 82 ]. Nonetheless, a few studies have also associated the abundance of this genera with the incidences of subclinical enteritis and Eimeria infection in broiler chickens [ 83 , 84 ], emphasizing the cost-benefit effects of antibiotic use in poultry production and the need for more studies in this regard. Lachnoclostridium has been positively correlated with increased butyrate production with attendant gut health protection and pathogen control effects [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intervention has long been regarded as a vital way to decrease morbidity rate and increase production performance, which has attracted growing attention ( 37 , 38 ). As a recognized probiotic, Bacillus subtilis is widely applied in animal husbandry due to its strong stress resistance and positive effects on the host ( 39 , 40 ). For instance, Zhang et al demonstrated that Bacillus subtilis PB6 administration dramatically increased villus height and maintain intestinal mucosal barrier function of ducks ( 41 ).…”
Section: Discussionmentioning
confidence: 99%